2012
DOI: 10.1039/c2sm07017k
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the dynamics of adsorption and of a transient interfacial stress on the formation of aggregates of IgG antibodies

Abstract: It is common knowledge that aggregation of proteins may occur in aqueous solutions under mechanical stress (shaking or high shear), even in solutions that are stable at rest. Addition of surfactants is a practical generic means to prevent this stress-induced aggregation (e.g. in formulations of therapeutic proteins), which suggests that interfaces contribute to destabilization. We studied here the role of interfacial stress by applying brief mechanical impacts on air-water interface, in presence or absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
95
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 39 publications
12
95
0
Order By: Relevance
“…The sloughing off and/or mechanical rupture of such films leads to subvisible particles in solution. 21,22 Protein particle formation in IV bags due to protein adsorption to interfaces was also suggested by Kumru, et al , and they observed a reduction in protein particles in the presence of polysorbate 20, an effect attributed to inhibition of protein adsorption to the bag walls and to the air-water interface. 14 …”
Section: Introductionmentioning
confidence: 60%
“…The sloughing off and/or mechanical rupture of such films leads to subvisible particles in solution. 21,22 Protein particle formation in IV bags due to protein adsorption to interfaces was also suggested by Kumru, et al , and they observed a reduction in protein particles in the presence of polysorbate 20, an effect attributed to inhibition of protein adsorption to the bag walls and to the air-water interface. 14 …”
Section: Introductionmentioning
confidence: 60%
“…While visible bubble formation was minimal at 1 mg/ ml, the contribution of air bubbles to particle formation cannot be entirely ruled out. The disruption of air bubbles could cause additional disruption of the air-water interface that leads to particle formation, as has been demonstrated by disruption of the hydrophobic interface previously (18). An IA of >∼305 mm 2 was found to promote particle formation for this bioconjugate under the studied experimental conditions and time scales.…”
Section: Discussionmentioning
confidence: 72%
“…Proteins migrate to the air-water interface (11) and unfold (12) causing aggregation and particle formation (13,14); data supporting this concept can be found in the literature (8)(9)(10). Additionally, agitation may be necessary for induction (10,15,16) and can synergistically worsen aggregation (17,18). …”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations